Studi Riview Literatur : Game Theory tentang Transportasi Online - Trisiya, Kapita Ayu; Fitria, Nabila; Hasibuan, Mega Utami; Hidayati, Nadia; Humayra, Lutfia; Harahap, Marwah Mahfuzah; Rachma, Dianny; Br Ginting, Siti Salamah (Journal of Multidisciplinary Inquiry in Science, Technology and Educational Research, 2025)
This article discusses the application of game theory in online transportation, focusing on public transportation management, traffic congestion, and passenger behavior. The study highlights how game theory can optimize decision-making among stakeholders, analyze competitive strategies among service providers, and improve traffic management. A literature review method is used to collect data from various sources, revealing insights into dynamic pricing strategies, user decision-making, and the impact of regulation on service providers. The study concludes that game theory is essential to understanding interactions in online transportation, while emphasizing the need for further research into the social impacts of these strategies and the evolving regulatory landscape.